Aberrant expression of p53, p16INK4a and Ki-67 as basic biomarker for malignant progression of oral leukoplakias - Nasser, Wasim; Flechtenmacher, Christa; Holzinger, Dana; Hofele, Christof; Bosch, Franz X. (Journal of oral pathology & medicine, 2011)
J Oral Pathol Med (2011) 40: 629-635 Background: The risk of malignant progression of oral leukoplakia with and without dysplasia is unpredictable. Materials and methods: Leukoplakias without dysplasia of 35 patients, leukoplakias with dysplasia of 4 patients, and similar lesions obtained from tumor patients were retrospectively examined by immunohistochemistry for the expression of the proteins pRb, p53, p16INK4a, Cyclin D1 and Ki-67. The predictive power of combined aberrant expression patterns for the progression of leukoplakias without dysplasia was examined. Results: Increased expression of p53, Ki-67 and Cyclin D1, and loss of p16INK4a occurred in 45.9%, 38.9%, 29.4% and 32.4% of the leukoplakias without dysplasia, respectively. All alterations increased with progression but had poor positive predictive value. However, the combined p53/p16INK4a/Ki-67 aberration occurred in only three (9%) cases, of which two patients (66.7%) experienced progression to dysplasia and carcinoma in situ. The combined p53/p16INK4a/Ki-67 alteration had a negative predictive value (NPV) and sensitivity of 100%, specificity of 97% and positive predictive value (PPV) of 67%. By contrast, the combined p53/p16INK4a/Cyclin D1 alteration had 97% NPV and sensitivity of 50%, specificity of 90% and only 25% PPV. Loss of pRb and concomitant overexpression of p16INK4a were not observed arguing against an involvement of HPV in oral leukoplakia. Conclusions: We propose the combined p53/p16INK4a/Ki-67 alteration as a basic marker to define high risk leukoplakia patients. Lesions not showing this alteration appear to be harmless. Future studies should validate these findings and search for proteins which can further improve the PPV of the proposed basic marker.
Im Titel ist "INK4a" hochgestellt
Gesehen am 21.09.2022